Penguasaan Bahasa Kedua pada Anak Usia Dini di Desa Sari Murni Kecamatan Randangan Kabupaten Pohuwato: Penelitian - Paramita Bumulo; Dakia N. Djou; Ellyana Hinta (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research discusses second language mastery in early childhood, especially in Sari Murni Village, Randangan District, Pohuwato Regency, based on the objectives of (1) Describing second language mastery at the phonological level in early childhood in Sari Murni Village, Randangan District, Pohuwato Regency (2) Describing second language mastery at the morphological level in early childhood in Sari Murni Village, Randangan District, Pohuwato Regency. The method used is descriptive qualitative. The data in this research was collected through observation techniques and listening techniques which include listening, taking notes and recording techniques. The data was analyzed by transcribing, grouping the data based on the level of second language acquisition, conducting analysis, and drawing conclusions. This research concludes that the ability of young children in Sari Murni Village to master Indonesian as a second language is at a stage of development that is not yet optimal, which reflects the complex dynamics in the language acquisition process.